Gene transcription during exposure to, and recovery from, cold and desiccation stress in Drosophila melanogaster. - Sinclair, B.J.; Gibbs, A.G.; Roberts, S.P. (Insect Molecular Biology, 2007)
We exposed adult male Drosophila melanogaster to cold, desiccation or starvation, and examined expression of several genes during exposure and recovery. Frost was expressed during recovery from cold, and was up-regulated during desiccation. Desiccation and starvation (but not cold) elicited increased expression of the senescence-related gene smp-30. Desat2 decreased during recovery from desiccation, but not in response to starvation or cold. Hsp70 expression increased after 1 h of recovery from cold exposure, but was unchanged in response to desiccation or starvation stress, and Hsp23 levels did not respond to any of the stressors. We conclude that D. melanogaster's responses to cold and desiccation are quite different and that care must be taken to separate exposure and recovery when studying responses to environmental stress.